An Empirical Analysis of the Impact of Public Expenditures on Education and Health on Poverty in Indian States - Raghbendra Jha; Bagala Biswal; Urvashi D. Biswal (Queen's University, Department of Economics, 2001)
The principal objective of this study is to test whether public expenditures on education, health and other development activities have been effective in reducing poverty in India. To ensure sensitivity and robustness of the results, three different measures of poverty belonging to the Foster-Greer-Thorbecke group of poverty measures are used. We consider various types of education expenditures, viz., government expenditures on elementary, secondary, higher/university and "other" levels. Data for fourteen Indian states from 13th to 53rd rounds of National Sample Survey of India are used for estimating poverty. Using unbalanced panel data techniques, we test Fixed effects, Random effects and OLS models, and conclude that education, health and development expenditures help reduce poverty. In particular, expenditure on higher, university, technical, adult and vocational educations as opposed to elementary and secondary education is more effective in poverty reduction. Several policy conclusions are advanced.
Keywords: H5; H51; H52; H53; I0; I3; O5; O15; O53; 330; India; Poverty Indices; Public Expenditures on Education and Health; Fixed and Random Effect Models; Panel Data